RETRACTED ARTICLE: Bridge the gap caused by public health crises: medical humanization and communication skills build a psychological bond that satisfies patients - Xiaoou Bu; Yao Wang; Yawen Du; Chuanglu Mu; Wenjun Zhang; Pei Wang (BMC, 2024)
Abstract Background Patient satisfaction is an important outcome domain of patient-centered care. Medical humanization follows the patient-centered principle and provides a more holistic view to treat patients. The COVID-19 pandemic posed significant barriers to maintaining medical humanization. However, empirical study on the relationship between medical humanization and patient satisfaction is clearly absent. Objectives We examined the mediation effects of communication on the relationship between medical humanization and patient satisfaction when faced with a huge public health crisis like the COVID-19 pandemic, and the moderation effect of medical institutional trust on the mediation models. Methods A cross-sectional survey study was performed. A final sample size of 1445 patients was surveyed on medical humanization, communication, patient satisfaction and medical institutional trust. Results All correlations were significantly positive across the main variables (r = 0.35-0.67, p < 0.001 for all) except for medical institutional trust, which was negatively correlated with the medical humanization (r=-0.14, p < 0.001). Moderated mediation analysis showed that the indirect effect of medical humanization on patient satisfaction through communication was significant (b = 0.22, 95% CI: 0.18 ~ 0.25). Medical institutional trust significantly moderated the effect of medical humanization on patient satisfaction (b=-0.09, p < 0.001) and the effect of medical humanization on communication (b= -0.14, p < 0.001). Conclusion Medical humanization positively influence patient satisfaction, communication mediated the association between medical humanization and patient satisfaction, and medical institutional trust negatively moderated the effects of medical humanization on patient satisfaction and communication. These findings suggest that humanistic communication contributes to patient satisfaction in the face of a huge public health crisis, and patients' evaluation of satisfaction is also regulated by rational cognition.